2017
DOI: 10.1253/circj.cj-16-0921
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Bicarbonate-Ascorbic Acid Combination for Prevention of Contrast-Induced Nephropathy in Chronic Kidney Disease Patients Undergoing Catheterization

Abstract: ography and intervention. 11 Similarly, although Spargias et al reported that ascorbic acid protected against CIN in high-risk patients undergoing a coronary procedure, 12 the REMEDIAL trial could not prove the superiority of ascorbic acid. 13 No published studies have examined the efficacy of combined i.v. sodium bicarbonate and ascorbic acid for the prevention of CIN. The aim of the current prospective randomized trial was therefore to determine whether i.v. sodium bicarbonate and ascorbic acid, in addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In the general population, the incidence of CI-AKI is 2.0%, but in the population with comorbid chronic kidney disease, diabetes, advanced age, and emergency percutaneous coronary intervention (PCI), the incidence of CI-AKI rises to 30% [24]. Although studies have shown that some drugs or methods have a preventive effect on CI-AKI, such as lignans [25], acetylcysteine[26], sodium bicarbonate [27], hydration[28]etc. But, there is still no consensus on these methods.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, the incidence of CI-AKI is 2.0%, but in the population with comorbid chronic kidney disease, diabetes, advanced age, and emergency percutaneous coronary intervention (PCI), the incidence of CI-AKI rises to 30% [24]. Although studies have shown that some drugs or methods have a preventive effect on CI-AKI, such as lignans [25], acetylcysteine[26], sodium bicarbonate [27], hydration[28]etc. But, there is still no consensus on these methods.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, the incidence of CI-AKI is 2.0%, but in the population with comorbid chronic kidney disease, diabetes, advanced age, and emergency percutaneous coronary intervention (PCI), the incidence of CI-AKI rises to 30% [24]. Although studies have shown that some drugs or methods have a preventive effect on CI-AKI, such as lignans [25], acetylcysteine [26], sodium bicarbonate [27], hydration [28]etc. But, there is still no consensus on these methods.…”
Section: Western Blotmentioning
confidence: 99%
“…Ascorbic acid exerts an antioxidant action against ROS and potentiates the effects of other antioxidants. Ten RCTs on ascorbic acid for CIN prevention have been conducted, among which 6 RCTs were published after 2011 [241,252,257,[270][271][272][273][274][275][276]. All of the studies targeted patients undergoing cardiovascular interventions, and no study targeted patients who received intravenous contrast media.…”
Section: Rationale Cq 8-3mentioning
confidence: 99%